Implementation of Ice Breaking on PJOK Learning Motivation - Savitri, Vira Nur; Santosa, Agus; Kurnia, Dedi (Journal of Physical and Outdoor Education, 2023)
This study aims to determine the implementation of ice breaking on student learning motivation. The research method used is Experiment. The population of grade 5 SDN 1 Wanayasa was 32 students, sampling was carried out using the Total Sampling technique, the research sample amounted to 32 students. The research instrument used a questionnaire (questionnaire). Hypothesis testing using paired Sample T test, which is to test the normality and homogeneity of the research data Because the significance value is less than 0.0020 <0.05, it can be concluded that the research data is accepted. The results of the increase from the Pre-test and Post-test increased by 5.7%. So it can be concluded that ice breaking can increase student learning motivation. So that it can spur students to be more active in the learning process at school.